A ordem: tempo analítico, homicídios e PCC no Triângulo Mineiro (1990-2020) - Marques, Thalia (2023)
Homicide rates have varied widely in Brazil, in time and space, over the past four decades (1990-2020). From the standpoint of their aggregate levels, these rates rise consistently until 2017 and then fall. Detained observations in individual states and regions, however, show rapid upward and downward variations on the same dates. This dissertation proposes an interpretation of this phenomenon. Studying the Triângulo Mineiro, I propose the idea of "analytical time" of factional expansion, the time of passage from one order of regulation of lethal violence to another, to understand these variations. To accomplish this, I present a multi-methodological study, because it deals with a complex, relational, and multi-causal phenomenon, as are homicides. It is quantitative concerning the compilation, production, and analysis of homicide rates, and qualitative in understanding the mechanisms involved in homicide cases, in three cities of the region: Uberlândia, Uberaba, and Cidade da Saúde. This methodological and analytical framework could, as hypothesized here, be used to think about homicide variations in a relational way, in the national context.